Respuesta :
Answer:
I. 6x2 + 25x + 24 = 0 6x2 + 16x + 9x + 24 = 0 2x (3x +8) + 3 (3x + 8) = 0 (2x + 3) (3x +8) ... < y=1; = x<y I. 10x2 + 33x + 27 = 0 => 10x2 + 15x + 18x + 27 = 0 => 5x (2x + 3) + 9 (2x + 3) = 0 => (5x +9) (2x +3) ... x = —9/5, –3/2 II. ... (b) 62 (d) is TX TX II.
21x - 27 = 0 (add the 3x + 18x together since they’re like terms)
21x = 0+27 (move the -27 to the other side of the = and when you do the sign will become the opposite eg “-“ will become “+” and a multiply will become a divide)
x = 27 ÷ 21
x = 1.29 or 9/7
what you have to do it try and get x on its own on one side of the = so you shift all the other things to the other side i guess
21x = 0+27 (move the -27 to the other side of the = and when you do the sign will become the opposite eg “-“ will become “+” and a multiply will become a divide)
x = 27 ÷ 21
x = 1.29 or 9/7
what you have to do it try and get x on its own on one side of the = so you shift all the other things to the other side i guess